Functional Assessment of Cancer Therapy Bone Marrow Transplantation: portuguese translation and validation - Mastropietro, Ana Paula; Oliveira, Érika Arantes de; Santos, Manoel Antônio dos; Voltarelli, Júlio César (Revista de Saúde Pública, 2007)
OBJECTIVE: To translate into Portuguese and validate the "Functional Assessment of Cancer Therapy - Bone Marrow Transplantation" (FACT-BMT) quality-of-life questionnaire, among bone marrow transplantation patients. METHODS: The study was carried out in Ribeirão Preto, Southeastern Brazil in 2005. After translating FACT-BMT (version 3) into Portuguese, it was applied to 55 consecutive leukemia patients simultaneously with the Portuguese version of the Short Form-36 Health Survey (SF-36). These patients had undergone transplantation and were being followed up. Two clinical parameters were used for testing the sensitivity of the questionnaire: time elapsed since transplantation and presence or absence of graft-versus-host disease. Analysis of variance with the post-hoc Tukey test was used. Cronbach's alpha coefficient was applied, standardized for all the questions, final scores and domains. RESULTS: The patients' mean age was 34.8±8.1 years and mean schooling was 10.8±4.7 years, and 78.1% of the patients were female. The mean time since transplantation was 29.8±32.19 months. At the end of the translation and cultural adaptation process, it was seen that there had not been any alteration to the original format of the questionnaire. The internal consistency was high (0.88). The correlation between the translated questionnaire and SF-36 ranged from 0.35 to 0.57 and was considered to be moderate to good for most quality-of-life domains. The evaluation of the construct and concurrent validities was satisfactory and statistically significant. CONCLUSIONS: The Portuguese version of FACT-BMT was satisfactorily validated for application to Brazilian patients of both sexes undergoing bone marrow transplantation.